DYNAMICS OF CHANGES IN THE ULTRASTRUCTURE OF RATS’ COLON MUCOSA CELLS OF IN THE AREA OF THE ANASTOMOSIS IN A SIMULATED VENOUS ISCHEMIA - Belozyorov, I.V. (World of Medicine and Biology, 2013)
Electron microscopic study of the dynamics of changes in the ultrastructural organization of cells of the colon after ligation, dissection and suturing of the colon in a simulated venous ischaemia shown that in the first seven days of degenerative disorders grow, grow into a destructive phase. By the tenth day of the experiment at the ultrastructural level, begin to develop the metabolic processes of growth and reparative activities. Already by the 14th day of the experiment ultrastructure of columnar epithelial cells and endothelial cells of the capillaries is restored. Remain only moderate degenerative changes that lie within the physiological compensation.
Keywords: ultrastructure of cells of the colon; ligation of the veins; ischemia; hypoxia